1998
DOI: 10.1017/s0950268898008802
|View full text |Cite
|
Sign up to set email alerts
|

M genotyping and DNA fingerprinting of Streptococcus pyogenes isolates from an area of central Italy

Abstract: M protein gene typing was used to analyse Streptococcus pyogenes clinical isolates collected between 1983 and 1995 in an area of central Italy from patients presenting different types of infections; the same isolates were also characterized by means of DNA fingerprinting. M type 1 was the most common (50% of study strains), followed by M types 4, 12 and 6. The proportion of M type 12 decreased with time, whereas M type 1 increased, in agreement with data obtained in many different areas. Most invasive strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The most serious paediatric infection we observed was an abdominal abscess due to streptococcal superinfection during varicella consistent with the widely reported view that children with varicella are clearly at a greater risk of GAS invasive infections [25]. M protein genotyping showed that emm types 1, 3, 4, 6, 12, 28 were the most frequent and our findings are in accordance with other studies from various areas, which indicate the wide distribution of the M types we observed [10,19,22,26]. The distribution of types appeared to vary from year to year and during the study period the proportion of isolates of types 1 and 12 fell, while types 3, 6, 22, 28, 77 emerged.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The most serious paediatric infection we observed was an abdominal abscess due to streptococcal superinfection during varicella consistent with the widely reported view that children with varicella are clearly at a greater risk of GAS invasive infections [25]. M protein genotyping showed that emm types 1, 3, 4, 6, 12, 28 were the most frequent and our findings are in accordance with other studies from various areas, which indicate the wide distribution of the M types we observed [10,19,22,26]. The distribution of types appeared to vary from year to year and during the study period the proportion of isolates of types 1 and 12 fell, while types 3, 6, 22, 28, 77 emerged.…”
supporting
confidence: 92%
“…Clinical isolates were identified as GAS by standard laboratory methods [21] Isolates were characterized by M protein genotyping, using two methods. First, PCR amplification of the M protein gene (emm gene) and subsequent hybridization with a panel of 10 M-specific probes in a reverse line blotting system, according to the method of Kaufhold et al [22] modified as previously described ; second, the variable M protein type-specific region of the emm gene was sequenced according to protocols developed by the Center for Disease Control [23]. The x 2 or Fisher's exact test was used for statistical analysis.…”
mentioning
confidence: 99%
“…The most common serotypes of strains isolated worldwide from pharyngitis and TSLS patients are M1 and M1/M3, respectively. However, these strains seemed not to possess fibronectin-binding proteins and/or their genes (12,30,32). In this study, we showed that all of the test strains from TSLS and non-TSLS patients possess the fbp54 gene with different serotypes of M protein (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…A few studies on the prevalence over time of M-protein serotypes among invasive GAS strains in Italy are available, but only small collections of isolates were analyzed. In those studies, the majority of strains belonged to emm types 1, 4, and 12, followed by types 28 and 77, with emm1 and emm12 declining over time and types 3, 22, and 77 appearing more recently (25,26).…”
Section: Discussionmentioning
confidence: 91%
“…(This work was presented in part at the XVIth Lancefield International Symposium on Streptococci and Streptococcal Diseases, 25 (21), 102 notifications of invasive infections and 89 GAS strains from patients with invasive infections were received. A case of invasive GAS disease was defined as isolation of the bacterium from a site that is normally sterile, like blood, cerebrospinal fluid, joint aspirates, pericardial and peritoneal fluids, bone, deep tissues, or abscesses, at the time of surgery or necropsy.…”
mentioning
confidence: 99%